MODEL PEMBELAJARAN AKIDAH AKHLAK DENGAN YOUTUBE CONTENT DALAM MENINGKATAN KECERDASAN SPIRITUAL SISWA - M. Masrur Huda; Moch. Adim; Moh. Jawani; Charidatul Muhsona (TA'LIM : Jurnal Studi Pendidikan Islam, 2022)
This journal examines the learning model of Islamic religious education teachers in improving the morality of students at MI Nahdlatul Ulama Kedungrejo Waru Sidoarjo. The purpose of this research is to know the learning of moral aqidah with Youtube Content. This research is a qualitative descriptive study using a spiritual, psychological, pedagogical approach. The types of data used in this study are primary data and secondary data. The research instrument uses an observation guide, interviews, and checks on documentation. The results show that the moral aqidah learning model with youtube content is used at MI Nahdlatul Ulama Kedungrejo. Expectations of students are good enough, namely students have started to be diligent in worship, discipline, responsibility, association and self-development.